Simulation of the Thermal Inertia of a Wall Under the Saharan Winter Climatic Conditions of Algeria - Khelifa Hami, AbdelkrimTalhi, Houcine Aissani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Thisworkinvolvesthestudyand the modelingofheat transferin awall subjectedtoaconditionofsolar radiationinwinteronthe outside. Anoptimalproposalis clearedfrom this studybased onthe searched objectives. Wealso analyzedtheinfluenceof heat transferonmaterials selectionand optimizationofthe thickness ofsuchabuilding envelopeinsouthwestAlgeria. The operationof thenumerical codedevelopedoncasesrelatedto theprobleminthehome.The simulation resultsarepresentedexamplesofbuildinginreal operating conditions(solar input, temperature, accumulated heat, etc....) and areingoodagreementwiththoseofthe literature. In the established periodic regime, the temperature of the outer face varies from 21.23°C to 56.01°C, the temperature in the middle of the wall varies from 14.96°C to 22.02°C. Therefore, the amplitude of the quasi-steady state is 17.39°C. The heat stored and returned inside the room varies from 136.61 W/m² to 177.73 W/m²; the amplitude of the quasi-stationary regime is 20.56 W/m²